2014
DOI: 10.1021/nn503000w
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Growth at the Two-Dimensional Limit on Ag(111)

Abstract: Having fueled the microelectronics industry for over 50 years, silicon is arguably the most studied and influential semiconductor. With the recent emergence of two-dimensional (2D) materials (e.g., graphene, MoS2, phosphorene, etc.), it is natural to contemplate the behavior of Si in the 2D limit. Guided by atomic-scale studies utilizing ultrahigh vacuum (UHV), scanning tunneling microscopy (STM), and spectroscopy (STS), we have investigated the 2D limits of Si growth on Ag(111). In contrast to previous report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
98
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 51 publications
11
98
2
Order By: Relevance
“…The peak shows a tail toward lower frequencies, that is similar to the one found in microcrystalline silicon due to amorphous/small grain regions [33]. Such a result is in agreement with a previous Raman analysis of the same phase [11].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The peak shows a tail toward lower frequencies, that is similar to the one found in microcrystalline silicon due to amorphous/small grain regions [33]. Such a result is in agreement with a previous Raman analysis of the same phase [11].…”
Section: Resultssupporting
confidence: 91%
“…The observation of these features is in clear contrast with the typical spectra obtained for silicon oxide materials, that are characterized by a broad and diffuse band centred at 440 cm −1 and a sharp but not too intense peak at 492 cm −1 [38,39]. Such a peak, that was also observed in the spectra of silicene monolayer and layers obtained for higher Si coverages when the samples were measured in air [11], is clearly absent in Fig. 6, suggesting some resistance to air of monolayer silicene in agreement with a previous work [40].…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…21 Takeda and Shiraishi 14 reported silicene for the first time in 1994 and Guzmán-Verri and Voon 15 coined its name in 2007. Although free-standing silicene is not stable, it was experimentally fabricated on Ag, [21][22][23][24] Ir, 25 ZrB 2 , 26 and ZrC. 27 Using firstprinciples calculations, various substrates such as h-BN, 28 SiC, 29 GaS, 30 graphene 31 and ZnS 32 which have weak van der Waals (vdW) interactions with silicene have been also studied to improve its stability.…”
Section: Introductionmentioning
confidence: 99%
“…Such thick Si films were first addressed to as "multi-layer silicene"; however, further studies revealed their diamond bulklike structure and the surfactant behaviour of silver atoms [33][34][35]. The determination of the atomic structure of the reconstructions is of profound interest, being closely related to the electronic bands simulated by DFT calculation.…”
Section: Introductionmentioning
confidence: 99%